2008
DOI: 10.1007/s11046-008-9133-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Phenotypic Switching in Cryptococcus neoformans Biofilms

Abstract: Cryptococcus neoformans is an encapsulated yeast-like fungus that is a relatively frequent cause of meningoencephalitis in immunocompromised patients and also occasionally causes disease in apparently healthy individuals. This fungus collectively forms biofilms on polystyrene plates and medical devices, whereas individually can undergo phenotypic switching. Both events have profound consequences in the establishment of fungal infection and are associated with persistent infection due to increase resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 22 publications
2
14
0
3
Order By: Relevance
“…Both mucoid switch variants (RC2-MC and NP1-MC) have altered cell walls and exhibit increased sensitivity to lysing enzyme. Cell charge and melanization are not affected by PS in the two switch systems; however, biofilm formation can differ in the switch variants [104]. …”
Section: Phenotypic Switchingmentioning
confidence: 99%
“…Both mucoid switch variants (RC2-MC and NP1-MC) have altered cell walls and exhibit increased sensitivity to lysing enzyme. Cell charge and melanization are not affected by PS in the two switch systems; however, biofilm formation can differ in the switch variants [104]. …”
Section: Phenotypic Switchingmentioning
confidence: 99%
“…Cryptococcus neoformans collectively forms biofilms on polystyrene plates and medical devices [6]. Martinez and Casadevall demonstrated that fungal biofilm formation is dependent on support surface characteristics and that growth in the biofilm state makes fungal cells less susceptible to potential environmental stresses, including antibiotics [7;8].…”
Section: Discussionmentioning
confidence: 99%
“…The capsule can be altered by phenotypic switching, which can also change the ability of C. neoformans to generate biofilms [94]. Conditions that mimic the host environment have been suggested to be permissive for biofilm formation [95].…”
Section: Molecular Studies Of Fungal Biofilmsmentioning
confidence: 99%
“…Quorum sensing is also described for C. neoformans [103], but its impact on biofilm formation is still unknown. There is evidence that certain cell variants exhibit higher switching rates when grown as biofilm-associated cells rather than planktonic cells [94]. …”
Section: Molecular Studies Of Fungal Biofilmsmentioning
confidence: 99%